'Chateaubriand ou rien, Hugo et tout': Contemplating the Poet's Posterity. (1st October 2016) - Stephens, Bradley
Abstract : Victor Hugo's vow as a teenager to become Chateaubriand ultimately surpassed even this audacious ambition. Today, Hugo casts an inescapable shadow across contemporary culture as nineteenth-century France's most iconic writer, as recent political, pedagogical, and popular discussions indicate. This article explores some of these examples so as to confirm Hugo's redoubtable cultural capital before asking: what did it actually mean in Hugo's eyes to equal his childhood idol's standing? By returning to Hugo's own understanding of what it meant to become a 'great man', the clichés of patriarchal authority that so often surround his oeuvre can be contested in order to allow for a more probing understanding of both his work and his enduring influence. A closing overview of this special issue of Dix-Neuf situates each of the diverse contributions along this critical line of thinking as an introduction to the scholarship that Hugo's work increasingly encourages in the twenty-first century.